Topographic Shelf Waves Control Seasonal Melting Near Antarctic Ice Shelf Grounding Lines. Issue 16 (29th August 2019) - Sun, Sainan; Hattermann, Tore; Pattyn, Frank; Nicholls, Keith W.; Drews, Reinhard; Berger, Sophie
Abstract: The buttressing potential of ice shelves is modulated by changes in subshelf melting, in response to changing ocean conditions. We analyze the temporal variability in subshelf melting using an autonomous phase‐sensitive radio‐echo sounder near the grounding line of the Roi Baudouin Ice Shelf in East Antarctica. When combined with additional oceanographic evidence of seasonal variations in the stratification and the amplification of diurnal tides around the shelf break topography (Gunnerus Bank), the results suggest an intricate mechanism in which topographic waves control the seasonal melt rate variability near the grounding line. This mechanism has not been considered before and has the potential to enhance local melt rates without advecting different water masses. As topographic waves seem to strengthen in a stratified ocean, the freshening of Antarctic surface water, predicted by observations and models, is likely to increase future basal melting in this area. Key Points: Variation in ice shelf basal melt rates is observed over a broad range of time scales, from tidal to seasonal Topographic shelf waves dominate the observed temporal melt rate variability in the study region Sea ice concentration and tidal currents modulate the magnitude and temporal variation of melt rates Plain Language Summary: Ice shelves (or the floating parts of the Antarctic ice sheet) lose primarily mass through melting at their bottom in contact with the ocean. This thins them and makes them more vulnerable to potential collapse. To understand the processes governing such thinning, direct and long‐time measurements are essential. Here we report on the first high‐resolution time series of direct melt measurements on the Roi Baudouin Ice Shelf in Dronning Maud Land during 2016. We find that subshelf melt varies on both seasonal and daily time scales. Temporal variations stem from topographical ocean waves that originate on the continental shelf and transfer ocean properties without time delay within the ice shelf cavity. Therefore, seasonal variations highly depend on the presence/absence of sea ice in front of the ice shelf, which impact the strength of topographical waves. This mechanism is highly efficient at increasing the ice‐ocean exchanges and may explain regional differences in ice shelf melt.